Thrombotic Thrombocytopenic Purpura: Three Peripartum Cases and Diagnostic Challenges. Issue 6 (January 2013) - Rahman, Wan Suriana Wan Ab; Abdullah, Wan Zaidah; Mustaffa, Rapiaah; Ahmed, Suhair Abbas; Hassan, Mohd Nazri; Husin, Azlan
Thrombotic thrombocytopenic purpura (TTP) is a medical emergency characterized by occlusive microangiopathy due to intravascular platelet aggregation. This event results in damage to the red blood cells (RBCs) known as microangiopathic hemolytic anemia (MAHA). Schistocytes are circulating fragments of damaged RBCs that have different morphological features including keratocytes, helmet cells, and spherocytes. It is critical to report even a small number of these abnormal RBCs in the peripheral blood and to be alert for the possible diagnosis of TTP, especially in unexplained anemia and thrombocytopenia. The application of pentad criteria in the diagnosis has been reviewed, and the challenges still remained on the hematologic evidence of this disorder. In the 3 cases discussed here, the red cell morphological diagnosis gave an impact on TTP diagnosis, but overdiagnosis might be encountered in obstetrical patients due to nonspecific diagnostic criteria.